RANCANG BANGUN PROTOTIPE ALAT PENERIMA PAKET DARI KURIR EKSPEDISI - Istiqomah Sumadikarta; Alfisyahrin Alsya; Hernalom Sitorus; Bosar Panjaitan (FAKULTAS TEKNIK, 2025)
Technological advances have driven the development of package delivery systems, particularly in e-commerce. However, challenges such as package loss and damage remain due to the lack of a secure receiving system. This study aims to design and build a prototype of an Internet of Things (IoT)-based package receiving device that can be accessed in real-time using the Telegram application. The research methods used include needs analysis, hardware and software design, and system testing. The hardware used includes an Arduino Uno as the main microcontroller, an ESP8266 as an IoT communication module, an ultrasonic sensor for package detection, a servo motor for the box opening and closing mechanism, and a push button for manual operation. The software was developed using the Arduino IDE and configured with a Telegram Bot to provide notifications to users. Test results show that this system is capable of performing well in receiving packages automatically, securing packages until they are picked up by the owner, and sending real-time notifications to users. Thus, this tool can be a solution in improving package receiving security in the digital era.